Differential Infectivities among Different Japanese Encephalitis Virus Genotypes in Culex quinquefasciatus Mosquitoes. - Yan-Jang S Huang; Susan M Hettenbach; So Lee Park; Stephen Higgs; Alan D T Barrett; Wei-Wen Hsu; Julie N Harbin; Lee W Cohnstaedt; Dana L Vanlandingham (Public Library of Science (PLoS), 2016)
During the last 20 years, the epidemiology of Japanese encephalitis virus (JEV) has changed significantly in its endemic regions due to the gradual displacement of the previously dominant genotype III (GIII) with clade b of GI (GI-b). Whilst there is only limited genetic difference distinguishing the two GI clades (GI-a and GI-b), GI-b has shown a significantly wider and more rapid dispersal pattern in several regions in Asia than the GI-a clade, which remains restricted in its geographic distribution since its emergence. Although previously published molecular epidemiological evidence has shown distinct phylodynamic patterns, characterization of the two GI clades has only been limited to in vitro studies. In this study, Culex quinquefasciatus, a known competent JEV mosquito vector species, was orally challenged with three JEV strains each representing GI-a, GI-b, and GIII, respectively. Infection and dissemination were determined based on the detection of infectious viruses in homogenized mosquitoes. Detection of JEV RNA in mosquito saliva at 14 days post infection indicated that Cx. quinquefasciatus can be a competent vector species for both GI and GIII strains. Significantly higher infection rates in mosquitoes exposed to the GI-b and GIII strains than the GI-a strain suggest infectivity in arthropod vectors may lead to the selective advantage of previously and currently dominant genotypes. It could thus play a role in enzootic transmission cycles for the maintenance of JEV if this virus were ever to be introduced into North America.